Etnobotânica e ecofisiologia de vegetações em cenários indígenas na região do Tapajós como indicadores de estudos de interação biosfera-atmosfera na Amazônia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2013)
The integration of ethnobotany and ecophysiology should be considered an alternative in the search for sustainability in the Amazon, since the ethnobotanical studies has shown the relationship between populations and plant resources and provides data on diversity, use and management of plants and ecophysiology evaluate the answers physiological interaction of plant / environment. In this context the joining of these tools can help identify species of extreme importance to the survival of certain populations and provide information about the physiology of these species, which helped draw managements plans adapted to local conditions. Thus, this study aimed to survey ethnobotanical species used in Novo Lugar Village, identifying the species of greatest cultural importance and characterize the stomatal responses. Therefore, interviews were conducted with application of semi-structured questionnaires to identify plants used, subsequently indexes of Frequency Relative Quotes and Value of usage were applied, which have shown the most important species. From this species, eight leaves expanded and asymptomatic disease for reading stomatal conductance were chosen, at random, through AP4 Porometer (ΔT Devices, Cambridge, England). Thus, we conclude that the families from Novo Lugar Village, has a vast knowledge of local flora; most plants is used in the preparation of medicines, the most important species for Borari Indians from Novo Lugar are: Andiroba (Carapa guianensis Aubl.), arruda (Ruta graveolens L.), arumã (Ischnosiphon obliquus (Rudge) Korn.), algodão roxo (Gossypium arboreum L.), banana (Musa sp.), buriti (Mauritia flexuosa L.), cupuaçu (Theobroma grandiflorum Schum), goiaba (Psidium guajava L.), ingá xixi (Inga heterophylla Willd.), murici (Byrsonima crassifolia (L.) Kunth) and urubucaá (Aristolachia trilobata L.); these species are physiologically different from each other, because they respond differently to the environment and that ethnobotany is a good bioindicator for studies of vegetation ecophysiology interest of the traditional community, it helps to understand the working of these species in current and future changes.
Keywords: Etnobotânica; Ecofisiologia; Povo Borari; Novo Lugar; CNPQ::CIÊNCIAS BIOLÓGICAS; INTERAÇÃO BIOSFERA ATMOSFERA